2018
DOI: 10.1002/slct.201801102
|View full text |Cite
|
Sign up to set email alerts
|

Sustenance of Inclusion Complexes of Ionic Liquid with Cyclic Oligosaccharide Molecules in Liquid and Solid Phases by Diverse Approaches

Abstract: The water soluble inclusion complexes of pyridinium based hydrophobic ionic liquid (IL) were prepared and characterised successfully. The inclusion complexes of sparingly soluble IL prepared with α‐ and β‐cyclodextrin in the mixed solvent medium and in solid state were studied by different physicochemical methodologies. Comparison of the chemical shift of the pure CDs, guest and complexes formed in 1‐H NMR spectra, appearance of the cross peaks in 2D‐ROESY spectra and shift in the band positions in FT‐IR spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 50 publications
(40 reference statements)
0
6
0
Order By: Relevance
“…All measurements were performed at 298.15 K using a 400 MHz spectrometer. Whenever a guest molecules gets encapsulated inside the hollow cavity of CD molecule, there happens some specific changes in the chemical shift values of the protons in the IC . From the structure of β‐CD molecule, it has been observed that H3 and H5 protons are placed inside the hollow cavity whereas other protons such as H1, H2 and H4 are present at the exterior of the cyclodextrin molecule (Scheme .)…”
Section: Resultsmentioning
confidence: 99%
“…All measurements were performed at 298.15 K using a 400 MHz spectrometer. Whenever a guest molecules gets encapsulated inside the hollow cavity of CD molecule, there happens some specific changes in the chemical shift values of the protons in the IC . From the structure of β‐CD molecule, it has been observed that H3 and H5 protons are placed inside the hollow cavity whereas other protons such as H1, H2 and H4 are present at the exterior of the cyclodextrin molecule (Scheme .)…”
Section: Resultsmentioning
confidence: 99%
“…In ICs no additional signal is obtained which deny the chance of chemical reaction. Thus, the study provides major information about the formation of the ICs in the solid state [32]. Fig.…”
Section: Ftir Studymentioning
confidence: 99%
“…During the formation of IC, the hydrophobic component of the drug (6-MP) molecule enters the hydrophobic hollow of the b-CD molecule, and no covalent link is formed or broken in the IC system. 67,68 Water molecules block the cavity of the b-CD molecule, which is an unfavourable situation. The water molecules are easily replenished when the hydrophobic region of the guest molecule enters the hollow chamber of the b-CD.…”
Section: Structural Inuences Of Oligosaccharidementioning
confidence: 99%